2023
DOI: 10.1002/bmb.21717
|View full text |Cite
|
Sign up to set email alerts
|

Perception of competence achievement and students' satisfaction using virtual laboratories in Medical Biochemistry course: Lessons from the COVID‐19 pandemic

Abstract: After the COVID‐19 pandemic, there was an increasing demand for remote learning and an expansion in the substitution of traditional practical sessions with lab‐based virtual tools. This study aimed to assess the effectiveness of virtual labs in practicing biochemical experiments and to examine the student's feedback regarding this tool. Virtual and traditional labs training were compared in teaching qualitative analysis of proteins and carbohydrates experiments for first‐year medical students. Students' achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…It was also found that these simulations increased students' interest in the course and their confidence in what they were learning. Considering these results from students point of view, these results are in line with previously described attitudinal analyses featuring VLs [2][3][4]8,15,16,28,34], and also are comparable with other virtual strategies implemented, such as gamification [27,37]. In contrast, teachers' opinions regarding the development of attitudinal competencies when using Labster virtual simulation activities differed from the results obtained in the student survey.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It was also found that these simulations increased students' interest in the course and their confidence in what they were learning. Considering these results from students point of view, these results are in line with previously described attitudinal analyses featuring VLs [2][3][4]8,15,16,28,34], and also are comparable with other virtual strategies implemented, such as gamification [27,37]. In contrast, teachers' opinions regarding the development of attitudinal competencies when using Labster virtual simulation activities differed from the results obtained in the student survey.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, more than 90% of the students preferred to use the Labster ® VLs as supplementary material prior to the face-to-face practical sessions. These results are consistent with those of other studies in which students accepted virtual labs, but still preferred to use them as preparation for classical labs [15]. Finally, the students' opinions about the use of virtual laboratory activities as complementary material to prepare traditional theoretical classes were highly positive and suggested that the use of these simulated activities can be easily expanded to subjects that do not include practical or laboratory activities in their curricula.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Controversially, other studies have found no effect of VL on students' knowledge [30,31]. For example, in the study by Ibrahim et al [32], two virtual biochemistry practices were used for university students. The results were contrasting when evaluating performance and knowledge assimilation; one of the tools showed a positive result, while the other showed low performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, virtual laboratories are often seen as a preparatory tool or complementary to in-person experiences by students and instructors [6,7,11]. The COVID-19 pandemic shifted this paradigm demonstrating that virtual learning can be implemented and effective as stand-alone skills training tools [1,12].…”
Section: Introductionmentioning
confidence: 99%